Geographical pattern of genetic diversity in Capsella bursa‐pastoris (Brassicaceae)—A global perspective. Issue 1 (13th November 2020) - Wesse, Christina; Welk, Erik; Hurka, Herbert; Neuffer, Barbara
Abstract: We analyzed the global genetic variation pattern of Capsella bursa‐pastoris (Brassicaceae) as expressed in allozymic (within‐locus) diversity and isozymic (between‐locus) diversity. Results are based on a global sampling of more than 20, 000 C. bursa‐pastoris individuals randomly taken from 1, 469 natural provenances in the native and introduced range, covering a broad spectrum of the species' geographic distribution. We evaluated data for population genetic parameters and F ‐statistics, and Mantel tests and AMOVA were performed. Geographical distribution patterns of alleles and multilocus genotypes are shown in maps and tables. Genetic diversity of introduced populations is only moderately reduced in comparison with native populations. Global population structure was analyzed with structure, and the obtained cluster affiliation was tested independently with classification approaches and macroclimatic data using species distribution modeling. Analyses revealed two main clusters: one distributed predominantly in warm arid to semiarid climate regions and the other predominantly in more temperate humid to semihumid climate regions. We observed admixture between the two lineages predominantly in regions with intermediate humidity in both the native and non‐native ranges. The genetically derived clusters are strongly supported in macroclimatic data space. The worldwide distribution patterns of genetic variation in the range of C. bursa‐pastoris can be explained by intensive intra‐ and intercontinental migration, but environmental filtering due to climate preadaption seems also involved. Multiple independent introductions of genotypes from different source regions are obvious. "Endemic" genotypes might be the outcome of admixture or of de novo mutation. We conclude that today's successfully established Capsella genotypes were preadapted and found matching niche conditions in the colonized range parts. Abstract : In the current literature, the colonization history of Shepherd's Purse ( Capsella bursa‐pastoris ) has been traced by molecular markers for certain regions. However, a worldwide consideration of the entire range of the species is still missing. Here, we provide the worldwide distribution patterns of genetic variation that can be explained by environmental filtering due to climate preadaptation.